ENSAIO CLÍNICO COMPARATIVO DA EFICÁCIA ANESTÉSICA DA ARTICAÍNA E MEPIVACAÍNA - Smolarek, Priscila de Camargo (2016)
Local anesthetics are drugs widely used by dentists. The objective of this doubleblind, crossover clinical trial was to evaluate the efficacy of articaine 4% (Ar4) compared to mepivacaine 2% (Me2) both associated with epinephrine 1: 100,000. The local anesthetics were applied to sound soft tissue (lower lip mucosa) in a model without surgical trauma. After sample size calculation, 72 healthy volunteers were randomly divided in two groups that received local anesthesia with Ar4 and Me2. A initial evaluation was performed to identify the physiological profiles of the volunteers. Then, they were blindfolded and subjected to baseline tests for sensitivity (A-alpha fibers A - beta, A - delta and fiber type C) and vascularization of the lower lip. Computerized anesthesia was subsequently performed. A total volume of 0.3 ml of anesthetic was injected in the central region of the lower lip. Pain during anesthesia was evaluated through the visual analogue scale (VAS). At different periods after anesthesia (3, 10, 20 and 30 min), all the tests were repeated. In addition to that, the diameter of the anaesthetized area was measured in mm, the residual effect of the anesthesia was assessed with the VAS (after 30, 40, 50 and 60 min), and the anesthesia recovery time in minutes (a self-assessment record). After 7 days, the cross-over was performed and the entire sequence of the tests was repeated. When considering the local vasoconstriction after anesthesia, the highest values were achieved after anesthesia with Me2, regardeless the evaluation period. The best anesthetic effect was observed for Me2, 20 and 30 minutes after anesthesia (p<0.001). Recovery from anesthesia was faster for Ar4 (average time of recovery = 81.51 ± 29.08 min) compared to Me2 (92.38 ± 26.82 min) (p = 0.001, Wilcoxon Signed Rank Test). In conclusion, the data collected in this research showed that the use of mepivacaine promoted a longer lasting anesthetic effect when compared with articaine.